1968
DOI: 10.1177/001872086801000401
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Operator's Handedness on Some Directional Stereotypes in Control-Display Relationships

Abstract: Recommendations about preferred directions of movement for controls and displays are based almost exclusively on right-handed persons. This experiment has studied some common control-display movement stereotypes to find out if these stereotypes are equally valid for left- and right-handed subjects. Our apparatus presented a scale that could be oriented horizontally or vertically. The numbers on the scale increased either right-to-left or left-to-right for the horizontal scales, or up-to-down or down-to-up for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It is seen that there is a handedness and hand-used effect in these data. The effects may be summarised as follows (quoting from [10]):…”
Section: Postulation Of a Hand/control Location Effect (A) Two-dimensmentioning
confidence: 99%
“…It is seen that there is a handedness and hand-used effect in these data. The effects may be summarised as follows (quoting from [10]):…”
Section: Postulation Of a Hand/control Location Effect (A) Two-dimensmentioning
confidence: 99%
“…Chapanis and Gropper [10] tested a group of 64 subjects who were left or right-handed using their left and right hands. They investigated stereotypes for horizontal and vertical displays where the control was always located below the display (two-dimensional).…”
Section: Postulation Of a Hand/control Location Effect (A) Two-dimensmentioning
confidence: 99%
“…There are known effects of the handedness of the person and the hand used in making control movements (Bradley, 1959; Chapanis & Gropper, 1968; Holding, 1957a, 1957b; Verhaegen et al, 1975). The data from these sources have been reanalyzed by Hoffmann (2009), where it was shown that the effects can be largely accounted for by the grasp of the fingers on the control so that the hand makes a “natural” rotation of the thumb toward the first finger.…”
Section: Introductionmentioning
confidence: 99%